"There's an alligator!": An approach to the study of the poem A la Laguna de Bay by Fernando Canon - Tardío, Beatriz Álvarez (Animo Repository, 2021)
Perseverance is the key to understanding Fernando Canon, a man who participated in the most important events of Philippine history at the turn of the 20th century. He was an Ilustrado who fought with the Katipunan revolution; helped Rizal distribute his novel Noli me tangere in the Philippines in 1887; acted as a member of the Malolos Congress; taught in 1908 at the School of Engineering and Architecture; served as Secretary of the University of the Philippines' Conservatory of Music upon its foundation in 1916; and wrote and published essays and poetry. When he was almost 60 years old, he fulfilled his childhood promise to his friend, José Rizal, and published this narrative poem A la Laguna de Bay in 1921. This paper unveils Canon's aim, which was to show how Philippine esoteric knowledge and spirituality can intertwine with technology, philosophical thinking, and modernity. It explains how the poem envisions the stages of a process towards a mutual understanding and cooperation between the modern and traditional knowledge that would nurture the spirit of the Filipino people. This union is conveyed in the poem through the adventures of the two main characters' experiences together in their journey along La Laguna de Bay. © Ateneo de Manila University.